Comparison of Genotypic and Phenotypic Methods of Metallo-β- lactamase Detection in Acinetobacter spp. - Batra, Priyam (J Glob Infect Dis, 2020)
INTRODUCTION: MBL containing genes have been reported in all GNBs including Acinetobacter spp since 1990s which are worrisome as they are transmitted by mobile genetic elements. Thus, early detection of MBL encoding organisms is necessary. The current study was designed to identify the most sensitive cost-effective test which could be used as a screening test for detection of cabapenamase producing Acinetobacter isolates. METHODOLOGY: All consecutive strains of Acinetobacter spp isolated from various clinical samples were included. All isolates found resistant to any of the carbapenems were tested for MBL production using MHT (on MacConkey Agar and Mueller Hinton Agar), Etest (using Imipenem/Meropenem-EDTA) and Combined Disc Test (using EDTA and 2 MPA as inhibitors and Ceftazidime/Imipenem/Meropenem as substrate discs). PCR was performed for representative strains for IMP, VIM, KPC, OXA and NDM-1 gene. RESULTS: Total of 154 non-duplicate strains of Acinetobacter spp were isolated and identified, of which, 134 (88%) and 126 (82%) were resistant to meropenem and imipenem respectively. All 134 meropenem resistant strains were tested for MBL production and PCR was performed on 100 strains. 3(3%), 5(5%), 7(7%), 26(26%), and 51(51%) strains had IMP gene, VIM gene, KPC gene, OXA gene and NDM-1 gene. MHT on MAC had better performance than on MHA and dilution to 0.05 McFarland was not required. CONCLUSION: MHT on MAC had best sensitivity when compared with gold standard PCR and was also cost effective. With ROC curve, we found that 2MPA was not a good MBL inhibitor when compared with EDTA..